Linear optical susceptibilities of the oxoborate (Pb 3O) 2(BO 3) 2WO 4: Theory and experiment - Ali Hussain, Reshak, Prof. Dr. (Springer Science+Business Media, 2014)
Link to publisher's homepage at http://link.springer.com/